Tunable Open‐Access Microcavities for Solid‐State Quantum Photonics and Polaritonics. Issue 10 (7th August 2019) - Li, Feng; Li, Yiming; Cai, Yin; Li, Peng; Tang, Haijun; Zhang, Yanpeng
Abstract: Optical microcavities are powerful platforms widely applied in quantum information and integrated photonic circuits, among which the open‐access microcavity is a newly emerging cavity structure consisting of a micro‐sized concave mirror and a planar mirror controlled individually by groups of nanopositioners, whilst light emitters can be grown or transferred at the antinode of the cavity optical modes. Compared with monolithic microcavities, the open‐access microcavity enables the simultaneous realization of small mode volume, large‐range tunability, flexible structural engineering, and easiness for integration with external emitters, exhibiting extensive applications in the fields of solid‐state quantum photonics and polaritonics over the last decade. This review first introduces the basic theory and the construction methods of open‐access microcavities, followed by the recent advances of their applications in exciton‐polaritons, photon condensates, quantum light sources, and nanoparticle sensing. Abstract : The open‐access microcavity consists of two individually controlled cavity mirrors separated by a micro‐sized air gap, enabling simultaneously small mode volume, large‐range tunability, flexible structural engineering, and easiness for integration with external emitters. This review presents the basic concepts, fabrication, and applications of open‐access microcavities in a broad range of research fields including exciton‐polaritons, quantum light sources, and sensing.